Efficient and Precise Grinding of Sapphire Glass Based on Dry Electrical Discharge Dressed Coarse Diamond Grinding Wheel - Lu, Yanjun (Micromachines (Basel), 2019)
In this paper, in view of low grinding efficiency and poor ground surface quality of sapphire glass, the coarse diamond grinding wheel dressed by dry impulse electrical discharge was proposed to perform efficient and precise grinding machining of sapphire glass. The dry electrical discharge dressing technology was employed to obtain high grain protrusion and sharp micro-grain cutting edges. The influences of grinding process parameters such as wheel speed, depth of cut and feed speed on the ground surface quality, grinding force and grinding force ratio on sapphire glass were investigated, and the relationship between grinding force and ground surface quality was also revealed. The experimental results show that the grain protrusion height on the surface of a coarse diamond grinding wheel dressed by dry electrical discharge can reach 168.5 µm. The minimum line roughness R(a) and surface roughness S(a) of ground sapphire glass surface were 0.194 µm and 0.736 µm, respectively. In order to achieve highly efficient ground quality of sapphire glass, the depth of cut was controlled within 7 µm, and the wheel speed and feed speed were 3000–5000 r/min and 10–20 mm/min, respectively. The influences of feed speed and wheel speed on grinding force ratio were more significant, but the influence of depth of cut was little.